Granulosa cell myoblastoma and alveolar soft tissue sarcoma - Reissenweber, Nelson J (Cirugía del Uruguay, 1973)
Anatomical characteristics of myoblastomas of granulous cells and alveolar sarcomas of soft parts are described, with stress on morphological differences and biological behaviour. The paper contains a brief summary of historical concept of both tumors. Histogenetic theories on its origin are discussed and neurogenic character is admited as the most Iikely, By means of histochemical detection techniques, the author finds great simi!arity between enzyme population of both tumors and sone components of nervous tissue.